KAJIAN SISTEM PENYULUHAN PERTANIAN DI PROVINSI MALUKU - , RAHIMA KALIKY ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to study the implementation and revitalization of agriculture extension